Focusing on Inattention: The Diagnostic Accuracy of Brief Measures of Inattention for Detecting Delirium. Issue 8 (26th March 2018) - Marra, Annachiara; Jackson, James C.; Ely, E. Wesley; Graves, Amy J.; Schnelle, John F.; Dittus, Robert S.; Wilson, Amanda; Han, Jin H.
Abstract : BACKGROUND: Delirium is frequently missed in most clinical settings. Brief delirium assessments are needed. OBJECTIVE: To determine the diagnostic accuracy of reciting the months of year backwards (MOTYB) from December to July (MOTYB‐6) and December to January (MOTYB‐12) for delirium as diagnosed by a psychiatrist and to explore the diagnostic accuracies of the following other brief attention tasks: (1) spell the word "LUNCH" backwards, (2) recite the days of the week backwards, (3) 10‐letter vigilance "A" task, and (4) 5 picture recognition task. DESIGN: Preplanned secondary analysis of a prospective observational study. SETTING: Emergency department located within an academic, tertiary care hospital. PARTICIPANTS: 234 acutely ill patients who were ≥65 years old. MEASUREMENTS: The inattention tasks were administered by a physician. The reference standard for delirium was a comprehensive psychiatrist assessment using Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision criteria. Sensitivities and specificities were calculated. RESULTS: Making any error on the MOTYB‐6 task had a sensitivity of 80.0% (95% confidence interval [CI], 60.9%‐91.1%) and specificity of 57.1% (95% CI, 50.4%‐63.7%). Making any error on the MOTYB‐12 task had a sensitivity of 84.0% (95% CI, 65.4%‐93.6%) and specificity of 51.9% (95% CI, 45.2%‐58.5%). The best combination of sensitivity and specificity was reciting the days of the week backwards task; if the patient made any error, this was 84.0% (95% CI, 65.4%‐93.6%) sensitive and 81.9% (95% CI, 76.1%‐86.5%) specific. CONCLUSION: MOTYB‐6 and MOTYB‐12 had very good sensitivities but had modest specificities for delirium, limiting their use as a standalone assessment. Reciting the days of the week backwards appeared to have the best combination of sensitivity and specificity for delirium.